Scalable programmable quantum gates and a new aspect of the additivity problem for the classical capacity of quantum channels - Winter, A. (IEEE International Symposium on Information Theory 2002, 2002)
We bring together two subjects in the realm of quantum information theory that might at first glance seem far apart: the theory of universal computation in a quantum computer, and noise resistant coding of classical information in quantum channels.